2014
DOI: 10.1186/1471-230x-14-117
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and prognosis of patients with hepatocellular carcinoma (HCC) in the non-cirrhotic liver

Abstract: BackgroundHCC predominantly develops in the condition of chronic inflammation that has led to liver cirrhosis. A small proportion of patients with HCC is diagnosed in the non-cirrhotic liver (NCL). Data on patients with HCC in NCL in advanced stages are scarce.MethodsA retrospective analysis was performed comparing 93 patients with HCC in NCL to 571 patients with HCC in liver cirrhosis (LC) with respect to clinical and demographic characteristics. Also factors influencing survival in patients with HCC in NCL w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
114
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(126 citation statements)
references
References 33 publications
10
114
1
1
Order By: Relevance
“…In the current work, we observed an overall low mean age of patients (46 years) when compared to the situation prevailing in resource-rich countries where the tumor mostly occurs at an age that ranges from the late fifties to the early seventies (approximate mean age 65 years) [2125] . Our data are, however, similar to that reported in previous studies conducted on Cameroonian HCC cases and to other studies conducted in Central Africa countries like Gabon [26].…”
Section: Discussionmentioning
confidence: 99%
“…In the current work, we observed an overall low mean age of patients (46 years) when compared to the situation prevailing in resource-rich countries where the tumor mostly occurs at an age that ranges from the late fifties to the early seventies (approximate mean age 65 years) [2125] . Our data are, however, similar to that reported in previous studies conducted on Cameroonian HCC cases and to other studies conducted in Central Africa countries like Gabon [26].…”
Section: Discussionmentioning
confidence: 99%
“…Given the high number of patients with non cirrhotic NAFLD, screening for HCC in this population is not practicable [15] . Interestingly, the features of NAFLD-related HCC are similar to those of HCC of obese patients and of non-cirrhotic HCC, independently of the etiology [92,93] . Accordingly, it has been reported that obese patients have a relative risk of liver cancer of 189% relative to the 117% of overweight subjects [94] .…”
Section: Hcc In Nafld Chronic Hepatitismentioning
confidence: 84%
“…In patients without liver disease, HCC tends to be diagnosed at a more advanced age than in patients with cirrhosis and it is usually detected in latter stages (BCLC D in 51.6% vs 42% in patients with cirrhosis) due to the lack of screening; however, mortality in patients in intermediate stages is lower than that in patients with cirrhosis. In this group of patients, the BCLC classification correlates best with survival than other staging systems and their survival rates are better due to the possibility of providing curative treatment of larger lesions in turn, leading to decreased recurrences (27% vs 73%) and greater survival (81% vs 23%) [116,117] . Upon recent inclusion of molecular markers such as wtER, IGF and VEGF-1 in prognostic scoring systems such as CLIP, their precision has been favorable although they are not currently routinely used [118][119][120] .…”
Section: Prognosismentioning
confidence: 95%